Normative Values for Thumb Length in Central Indian Adult Population - Pawan Agarwal; M. R. Thatte; Mansi Saraf; Rajesh Bobba; Dhananjaya Sharma; Jagmoah Singh Dhakar (Indian Journal of Plastic Surgery)
Introduction This article aims to establish the relative thumb length in comparison to the index finger in central Indian adults.